An Insight Into The Behavioral Factors Affecting Investment Decision Making W.R.T. Punjab (Journal of Pharmaceutical Negative Results, 2023)
The growing regimen of behavioral finance has given birth to new research in this arena. Behavioral finance has unfolded new assumptions that stand in sharp contrast to the standard finance. The macro and micro behavioral finance talk about the inefficiencies of the financial markets and the bounded rationality of the investors. The present study brings into the forefront some common behavioral biases and the factors influencing the investment behavior of individual investors. The paper includes eight behavioral biases namely herding, home, anchoring, representative, overconfidence, gambler’s fallacy, hindsight and confirmation bias. A sample of 400 respondents has been taken from two cities of Punjab i.e. Jalandhar and Amritsar. The College and University teachers serve as the respondents for this study. Factor Analysis has been applied for studying the factors affecting investment behavior of respondents while making investment decisions.